2006
DOI: 10.1542/peds.2006-1379
|View full text |Cite
|
Sign up to set email alerts
|

Large Maternal Weight Loss From Obesity Surgery Prevents Transmission of Obesity to Children Who Were Followed for 2 to 18 Years

Abstract: Contrary to outcomes after intrauterine under- and overnutrition, the prevalence of overweight and obesity in children of mothers with large voluntary postsurgical weight loss was similar to that in the general population, with no increase in underweight. The results demonstrate the importance of potentially modifiable epigenetic factors in the cause of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
186
2
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(203 citation statements)
references
References 38 publications
5
186
2
10
Order By: Relevance
“…83 Maternal weight loss by pre-pregnancy bariatric surgery prevents transmission of obesity to children compared with the offspring of mothers who did not undergo the surgery and remained obese. 84 Gestational weight gain irrespective of pre-pregnancy body mass is positively associated with obesity at 3 years. 85 Higher birth weight is linked by strong epidemiological evidence to childhood, adolescent and adult obesity, as demonstrated by the large cohort studies showing a greater prevalence of overweight in individuals born large 32 as well as more recent clinical studies showing that mothers with a higher pre-pregnant body mass index or a larger mid-upper-arm circumference during pregnancy tend to have children with greater adiposity at the age of 9 years.…”
Section: The 'Early-life Hypernutrition' Pathwaysmentioning
confidence: 97%
“…83 Maternal weight loss by pre-pregnancy bariatric surgery prevents transmission of obesity to children compared with the offspring of mothers who did not undergo the surgery and remained obese. 84 Gestational weight gain irrespective of pre-pregnancy body mass is positively associated with obesity at 3 years. 85 Higher birth weight is linked by strong epidemiological evidence to childhood, adolescent and adult obesity, as demonstrated by the large cohort studies showing a greater prevalence of overweight in individuals born large 32 as well as more recent clinical studies showing that mothers with a higher pre-pregnant body mass index or a larger mid-upper-arm circumference during pregnancy tend to have children with greater adiposity at the age of 9 years.…”
Section: The 'Early-life Hypernutrition' Pathwaysmentioning
confidence: 97%
“…Gestational weight gain irrespective of pre-pregnancy weight is positively associated with obesity at the age of 3 years (19) and even moderate weight gain between successive pregnancies has been shown to result in a significant increase in large for gestational age births (20) . However, maternal weight loss through bariatic surgery prevents the transmission of obesity to children compared to the offspring of mothers who did not undergo the surgery and remained obese (21) .…”
Section: The Developmental Origins Of Human Cardio-metabolic Diseasementioning
confidence: 99%
“…1,2 The evidence is now overwhelming that the risk is increased for large for gestational age (LGA) infants to be born to women who are overweight or obese when they become pregnant, who gain excess weight during pregnancy, who smoke during pregnancy, who develop gestational diabetes or who are older at first pregnancy. [1][2][3][4][5][6][7] Being LGA portends a much higher risk of obesity later in childhood and adulthood, with odds ratios as high as 15 compared with normal weight newborns. 1 Black children born LGA were 2.5-fold more likely to be obese at ages 2-5 than average weight babies, and had a 30% prevalence of obesity.…”
mentioning
confidence: 99%
“…The consequences of weight loss in obese women before pregnancy on weights of offspring at birth and through young adulthood are shown by the study of Kral et al 4 These authors identified women who had pregnancies before and after they had undergone bariatric surgery. All of the women were very obese at the time of the first pregnancy and had lost an average of over 15 BMI units by the time of the second pregnancy.…”
mentioning
confidence: 99%